Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences

Représentation des femmes expertes en environnement dans les médias écrits québécois – Boutique - Réseau femmes et environnement (2022)
Les femmes expertes en environnement sont-elles sous-représentées dans les médias écrits québécois❓ C’est pour répondre à cette question que le Réseau des femmes en environnement a réalisé une étude exploratoire sur le sujet. Dans le cadre de cette étude : ➾ La littérature et les données récentes sur le sujet ont brièvement été explorées; ➾ 125 articles québécois tirés de la revue de presse produite par Copticom pour sa communauté de pratique en communication climatique ont été analysés ; ➾ Dix entrevues individuelles ont été menées auprès de journalistes et de femmes expertes souvent citées dans les médias relativement à des enjeux environnementaux ou de santé. Le Réseau a été accompagné dans cette démarche par Selma Vorobief, conseillère en évaluation participative et en recherche-action.
Keywords: 2000 à aujourd'hui; amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; discipline; environnement; médias; périodes historiques; québec; régions géographiques; santé; sciences; systèmes d'oppressions; thématiques; travail; violences